Reflections of Learning Experiences of International Students in Sweden - Uusimaki, Liisa; Garvis, Susanne (Journal of International Students, 2020)
The purpose of this article is to present a qualitative study exploring a small cohort of nine international students’ in-depth reflections about their teaching and learning experiences studying at a major Swedish University. Interestingly while there have been numerous studies reporting on the experiences of international students attending Anglo-Saxon universities, few studies have explored teaching and learning experiences of international students studying in Sweden. Using Carol Rodgers (2002) model of four functions of reflections provided a novel way to explore international students’ reflections about their learning experiences in Sweden, especially how these are shown in the following different cycles, of presence, description, analysis and experimentation. Making sense of international students’ experiences allows us as university lecturers to enhance our understanding how to better support international students’ in their learning away from their home universities.